House of Daniel Weld at Washington and Union Park Streets, ca. 1861 - Unknown (Tufts Archival Research Center, 2005)
Street-level view west of the house of Daniel Weld, located on Union Park Street at Washington Street. Both a boy and a street light are visible on the sidewalk lining the northwest side of Washington Street. Built by Daniel Weld, ca. 1800 7 7/16 x 8 7/8, 7 3/4 x 9 1/8 overall Photographs